Overall survival, adverse events, and economic burden in patients with chronic lymphocytic leukemia receiving systemic therapy: Real‐world evidence from the medicare population. (18th March 2021) - Goyal, Ravi K.; Nagar, Saurabh P.; Kabadi, Shaum M.; Le, Hannah; Davis, Keith L.; Kaye, James A.
Abstract: Background: Information on overall survival (OS) and adverse events (AEs) in patients with chronic lymphocytic leukemia (CLL) is mostly available from clinical trials. We therefore conducted a population‐based retrospective cohort study to assess OS, incidence of AEs, and economic burden in real‐world practice among Medicare patients treated for CLL. Methods: Patients with CLL receiving ≥1 systemic therapy from 2013 to 2015 were selected from the Medicare claims database and followed from the start of first observed systemic therapy (index date) through December 2016 or death. OS for patients receiving each of the most commonly observed treatments was estimated by the Kaplan–Meier method. AEs were assessed among patients receiving these treatments across all observed lines of therapy. All‐cause direct medical costs were assessed from the Medicare system perspective. Results: Among 7, 965 eligible patients across all observed therapy lines, ibrutinib monotherapy (Ibr; n  = 2, 708), chlorambucil monotherapy (Clb; n  = 1, 620), and bendamustine/rituximab (BR; n  = 1, 485) were the most common treatments. For first observed therapy, 24‐month OS estimates for Ibr, Clb, and BR recipients were 69% (95% CI = 68%–71%), 68% (95% CI = 65%–71%), and 79% (95% CI = 77%–81%) respectively. The most frequently recorded AEs in patients receiving these treatments in any observed line of therapy were neutropenia, hypertension, anemia, and infection. For all patients, the mean monthly all‐cause cost during the follow‐up period was $8, 974 (SD = $11, 562); cost increased by the number of AEs, from $5, 144 (SD = $5, 409) among those with 1–2 AEs to $10, 077 (SD = $12, 542) among those with ≥6 AEs. Conclusion: Over two‐thirds of patients survived at least 2 years after starting their first observed therapy for CLL. Our findings highlight considerable susceptibility to AEs and unmet medical need in Medicare patients with CLL treated in routine practice. Medicare incurred substantial economic burden following initiation of systemic therapy, and patients with greater numbers of AEs accounted disproportionately for the high overall cost of CLL management. Abstract : A population‐based retrospective analysis was conducted to document treatment patterns, overall survival, adverse events, and economic burden in Medicare patients with chronic lymphocytic leukemia (CLL). Findings demonstrate that over two‐thirds of patients survived at least 2 years after the start of their first observed therapy during the study period and that greater number of adverse events were associated with higher economic burden of CLL.